2019
DOI: 10.1039/c9sc02357g
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular interactions between catalytic species allow rational control over reaction kinetics

Abstract: The non-covalent interactions between two phase-transfer catalysts allow tuning of reaction kinetics from bimolecular, to pseudo 0th order, to sigmoidal. Kinetic models and DFT calculations are used to obtain detailed insight in the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Although traditional studies of self-sorting focus on the nal equilibrium products, the kinetically controlled steady state intermediates with tunable structure and life-time could also play leading roles, if a meticulous design is considered. Moreover, endeavors should be made to couple various strategies including selfsorting, chemical fuel-driven assembly, 8-14 and catassembly, [48][49][50][51] together with other constitution elements especially the feedback loops, [52][53][54][55][56][57][58] to construct interaction networks that nally evolve into complex assembly systems, as shown by living beings. With the continuous inux of energy and matter that regulates the evolution process, new structures, patterns, functions, and even 'new chemistry' could emerge from sufficiently complex assembly systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although traditional studies of self-sorting focus on the nal equilibrium products, the kinetically controlled steady state intermediates with tunable structure and life-time could also play leading roles, if a meticulous design is considered. Moreover, endeavors should be made to couple various strategies including selfsorting, chemical fuel-driven assembly, 8-14 and catassembly, [48][49][50][51] together with other constitution elements especially the feedback loops, [52][53][54][55][56][57][58] to construct interaction networks that nally evolve into complex assembly systems, as shown by living beings. With the continuous inux of energy and matter that regulates the evolution process, new structures, patterns, functions, and even 'new chemistry' could emerge from sufficiently complex assembly systems.…”
Section: Discussionmentioning
confidence: 99%
“…Catalytic effect was due to a synergism between naphthyridine 35e and K2CO3, so for efficient autoregulation, the concentration of the salt should also be kept constant [135]. Further investigations showed that, while simple UPys had no catalytic effect on Michael additions, the ester functionalized derivative 92 was also able to act as a phasetransfer agent for K 2 CO 3 (similarly to the naphthyridine derivative 35e) and, thus, to catalyze Michael additions in CDCl 3 [136].…”
Section: Applications In Catalysismentioning
confidence: 99%
“…1 NCIs also facilitate dynamic interactions between reactive molecules, resulting in a single regulatory control typical of living systems. [2][3][4] In addition, macromolecular interactions inside a cell are managed by: (i) localizing the reactive compounds within the same subcellular compartment and (ii) keeping the reactive structures close to proteins, lipids or DNA via NCIs. 5 NCIs involving cationic species occur in side-chain interactions of proteins, 6,7 ion channels, [8][9][10] catalysis, 11,12 and antibody binding sites.…”
Section: Introductionmentioning
confidence: 99%